1996
DOI: 10.1021/je960180l
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Behavior of Mixtures. 3. Mixtures of Acetonitrile with Dimethylacetamide, Dimethyl Sulfoxide, Nitrobenzene, and Methanol at 25 °C

Abstract: Ultrasonic velocities (u), densities (ρ), viscosities (η), relative permittivities (ε), and refractive indicies (n D) of mixtures of acetonitrile with dimethylacetamide, dimethyl sulfoxide, nitrobenzene, and methanol have been measured at 25 °C. From u, ρ, and η, isentropic compressibilities (κs), and its deviation from ideal behavior and excess viscosities (Δη) have been computed. From n D and ε, the Kirkwood correlation factor, g, has also been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 4 publications
8
20
0
Order By: Relevance
“…(3) The density value of (0.936357 ± 0.000005) g · cm −3 for N ,N -dimethylacetamide at T = 298.15 K compares well with the values of 0.936076 g · cm −3 and 0.93659 g · cm −3 published by De Visser (4) and Bakshi. (5) Unfortunately, accurate density data for triethylphosphate are not available in the literature at T = 298.15 K. However, the value of (1.064182 ± 0.000005) g · cm −3 determined in the present work seems to be better than the value of 1.06826 g · cm −3 obtained by French at T = 296 K. (6) It has been found that the solubility of tetramethylammonium perchlorate in triethylphosphate is too small to yield density data that will lead to accurate values of the apparent molar volumes.…”
Section: Methodsmentioning
confidence: 99%
“…(3) The density value of (0.936357 ± 0.000005) g · cm −3 for N ,N -dimethylacetamide at T = 298.15 K compares well with the values of 0.936076 g · cm −3 and 0.93659 g · cm −3 published by De Visser (4) and Bakshi. (5) Unfortunately, accurate density data for triethylphosphate are not available in the literature at T = 298.15 K. However, the value of (1.064182 ± 0.000005) g · cm −3 determined in the present work seems to be better than the value of 1.06826 g · cm −3 obtained by French at T = 296 K. (6) It has been found that the solubility of tetramethylammonium perchlorate in triethylphosphate is too small to yield density data that will lead to accurate values of the apparent molar volumes.…”
Section: Methodsmentioning
confidence: 99%
“…Z m is the viscosity of the corresponding solvent mixture and Z 0 is the viscosity of pure ACN (viscosities were taken from ref. [51][52][53][54] and are all at 25.07C). The viscosity corrected mobilities (solid symbols) are presented in Fig.…”
Section: Effect Of Additivesmentioning
confidence: 99%
“…3. A small amount of MeOH or acetone in the BGE decreases the viscosity of the solution [52][53][54], and, thus, increases the mobility of the complex. Accordingly, the viscosity corrected mobilities are smaller than the uncorrected ones.…”
Section: Effect Of Additivesmentioning
confidence: 99%
“…The permittivity values of the binary solvent systems, MeCN-H 2 O and MeCN-MeOH, have been interpolated from the data from Ref. [44] and [45], respectively. …”
Section: Acknowledgementmentioning
confidence: 99%